Steady State and Transient Ultrasonic Field Modeling in Multilayered Liquid Using Distributed Point Source Method - Singh, Shavinder (My University, 2012)
In the field of non-destructive evaluation (NDE), the newly developed distributed point source method (DPSM) is gradually gaining popularity. DPSM is a semi-analytical technique used to calculate the ultrasonic fields (pressure, velocity and displacement fields) generated by ultrasonic transducers of finite dimension immersed in homogeneous or non-homogeneous media. In this work the technique is extended to model the transducer immersed in triple layered non-homogeneous fluid and the propagation of steady & transient wave and its pressure generated with transducer is placed at both normal and non-normal angles. DPSM is a frequency based technique. Wave propagation tone burst signal is used. For modeling of transient transmitted & reflected signals are observed at different locations & arrival times are studied. Input transient tone burst signal in time domain is transferred to frequency domain. These frequency components in DPSM module is executed & pressure values are computed at desired target points. Inverse FFT is used to convert the frequency domain results into time domain. Finally, key characteristics of ultrasonic wave propagation like location of Near Field Zone, Angle of Divergence (formulated in homogeneous fluid) & Snell's Law (formulated in triple layered non-homogeneous fluid) have been validated for the obtained results. The empirical & computed DPSM results are found to be matching with reasonable accuracy.
M.E. (CAD/CAM and Robotics)
Keywords: DPSM, Triple Layered Non-Homogeneous Fluid, Wave Propagation